ANALISIS PENGARUH LINGKUNGAN TOKO, VARIASI PRODUK, PROMOSI PENJUALAN, DAN LAYANAN TENAGA PENJUALAN TERHADAP KEPUASAN KONSUMEN (STUDI PADA ALFAMART H825 SEMARANG, JAWA TENGAH ) - Saputri, Fanny Setiyo; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2020)
Alfamart  H825, located  in  Semarang, Central Java  encounters  sale decreasing  28% in  2019 compared  to  2018  sale.  Based  on  interviews,  the  decline  in  sales  turnover  was  due  to  the emergence of a new competitor, Indomaret, which the location is close to Alfamart.  Besides, based on  customer  surveys,  they  were  not  satisfied  enough  with  the quality of  service  provided  by Alfamart such as the store environment, product availability, services, and limited promotions. Customer satisfaction is important to study because it covers consumer ratings of quality provided by the company in serving the needs of consumers and it roles as dependent variable that is influenced by the independent variables above. This research is aimed to explain the effect of store environment, assortment, services laborers, and sales promotion towards customer satisfaction at Alfamart Jl. Tirto Agung, Banyumanik, Semarang. This research was conducted using survey method and questionnaire that was measured using Likert scale towards the customers of the store. Firstly, questionnaire was distributed to respondents by researcher. Secondly, data are processed by SPSS application version 20. Thirdly, data are analyzed  by results of existing research and theories. Fourthly, draw conclusions based on the results of data analysis. There were 105 respondents who were at least, shopping twice per month in this store. The result shows that assortment has positive and significant effect   towards customers satisfaction and services laborer has positive and significant effect  towards customers satisfactiom while  store  environment  and  sales  promotion  have  not  positive  effect  towards  customers satisfaction. To increase consumer satisfaction, retail should provide a variety of product (assortment product) so that consumers freedom to choose products according their wants and needs. In addition, retails should improve the ability of salespeople to improve their ability to serve consumers. To increase consumer satisfaction, retailer should provide many assortment product so consumers can choose products that suit their wants and needs. In addition, retail should increases the seller's ability to increase quality of service for consumers.